The Moderating Role of Shariah Compliance in Millennials' Adoption of Digital Financial Transactions at Bank Muamalat - Irsyam, Muh; Syaparuddin; Marzuki, Sitti Nikmah; Strech, David E (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2024)
This study aims to analyze the moderating role of Sharia compliance in influencing the relationships between attitude, subjective norm, and perceived behavioral control variables towards the adoption of digital Islamic networks in financial transactions. Questionnaires were distributed to 204 respondents, and the data were analyzed using a regression approach with SmartPLS version 4 software, then interpreted through the Theory of Planned Behavior (TPB) concerning Sharia compliance. The results indicate that Sharia compliance and perceived behavioral control play a central role in shaping individual behavior in financial transactions. However, Sharia compliance has not been able to moderate attitude, subjective norm, and perceived behavioral control towards the adoption of digital Islamic networks. This suggests that Sharia compliance does not significantly influence how individuals form attitudes, subjective norms, or perceived behavioral control regarding the adoption of the technology. The study suggests that the paradigm shift in financial transactions within the Islamic community should encompass efficiency, transparency, and innovation in accordance with Sharia principles. These findings illustrate a fundamental shift in the convergence of religious values and advancements in financial technology. This study contributes pioneering insights to the literature, focusing on Sharia compliance. It introduces Sharia compliance as a significant moderating factor impacting perceived behavioral control and the adoption of digital Islamic networks.